DeSci Advancement and Gamification – Virtual University as A Model - Mikhaylov, Dmitry; Shafeeg, Abdulla; Shazhaev, Ilman (AI Society & STMIK Indonesia, 2023)
The existing model for knowledge dissemination that universities and research centers adopt relies on central funding and central repositories of publications and books which are for the most part guarded by pay walls. These central repositories manifest as for-profit Publishing houses. While the editing and peer review processes are fully voluntarily performed by experts in the scientific field, the outcome of the scientific work i.e. the publication remains under the publishing house ownership accessible only by paying an exorbitant fee. In conjunction, conventional brick and mortar universities nowadays stand as the main knowledge creation flocked by students. Again, access to these educational institutions and/or to research funding require substantial effort and/or cost from students and scientists alike. In this work we present a new model for the creation and dissemination of knowledge relying on the DeSci approach and crowd funding. The model circumvents many if not all of the deficiencies of the existing centralized approach.